2006
DOI: 10.1385/endo:30:2:237
|View full text |Cite
|
Sign up to set email alerts
|

The H723R Mutation in the PDS/SLC26A4 Gene Is Associated with Typical Pendred Syndrome in Korean Patients

Abstract: The fat gene in mice represents a recessive mutation at the carboxypeptidase E (Cpe) locus. The mutant allele (Cpe(fat)) encodes a highly unstable enzyme and produces an obesity phenotype characterized by attenuated processing of prohormones such as proinsulin that require this exopeptidase for full maturation. This article presents a preliminary physiologic and endocrinologic characterization of the stock of C57BLKS/LtJ-Cpe(fat)/Cpe(fat) mice at the backcross generation (N10) currently distributed by The Jack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In contrast, H723R, IVS7-2A>G, and IVS9+3A>G account for the majority of SLC26A4 mutations in East Asian populations. Combined with the results of Park et al (2004) and Cho et al (2006), our data indicate the H723R mutation accounts for approximately 40% of SLC26A4 mutations in Korea, which is similar to the 53% observed in Japanese patients [30,43]. Our observations confirm that H723R is the most frequently detected mutation in both Korean and Japanese populations, perhaps as a result of a common founder effect.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, H723R, IVS7-2A>G, and IVS9+3A>G account for the majority of SLC26A4 mutations in East Asian populations. Combined with the results of Park et al (2004) and Cho et al (2006), our data indicate the H723R mutation accounts for approximately 40% of SLC26A4 mutations in Korea, which is similar to the 53% observed in Japanese patients [30,43]. Our observations confirm that H723R is the most frequently detected mutation in both Korean and Japanese populations, perhaps as a result of a common founder effect.…”
Section: Discussionsupporting
confidence: 89%
“…The SLC26A4 gene, which is associated with enlarged vestibular aquaducts (EVA), is also a common causative gene of HL. Park et al (2005) demonstrated that 20 (83%) out of 24 probands with SLC26A4 mutations had at least one of three recurrent mutations (p.H723R, IVS7-2A>G or IVS9+3A>G) (15,18,24,25). In addition, the mtDNA A1555G mutation has been identified as the most prevalent mitochondrial mutation associated with HL in the Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…It is encoded from PDS/SLC26A4 gene (GenBank Accesion # NC_000007), located on chromosome 7q21-31 and spans approximately 57 Kb, with 21 exons. Pendrin mutations are typically inherited as autosomal recessive traits (OMIM 274600) [20].…”
Section: Introductionmentioning
confidence: 99%